2008
DOI: 10.1007/s10461-008-9378-0
|View full text |Cite
|
Sign up to set email alerts
|

A Population-based Survey of the Prevalence of HIV, Syphilis, Hepatitis B and Hepatitis C Infections, and Associated Risk Factors Among Young Women in Vitória, Brazil

Abstract: Objective-To estimate the prevalence of HIV, hepatitis B (HBV) and C (HCV) and syphilis infections and associated risk exposures in a population-based sample of young women in Vitória, Brazil. Methods-FromMarch to December 2006, a cross-sectional sample of women aged 18 to 29 years was recruited into a single stage, population-based study. Serological markers of HIV, HBV, HCV, and syphilis infections and associated risk exposures were assessed.Results-Of 1,200 eligible women, 1,029 (85.8%) enrolled. Median age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 12 publications
1
13
0
2
Order By: Relevance
“…Most Brazilian pregnant women had access to at least four prenatal consultations; however, variation in the number of visits is still signifi cant as a function of socioeconomic characteristics such as schooling and race or skin color. Therefore, the distribution of the investigated disease refl ects social inequalities in healthcare that have previously been observed by others in both Brazil 13,15,16 and other countries. 4,6,25 Inequalities in access to and the quality of prenatal care might somehow explain the higher exposure of children belonging to the less privileged classes to the risk of CS.…”
Section: Discussionsupporting
confidence: 55%
“…Most Brazilian pregnant women had access to at least four prenatal consultations; however, variation in the number of visits is still signifi cant as a function of socioeconomic characteristics such as schooling and race or skin color. Therefore, the distribution of the investigated disease refl ects social inequalities in healthcare that have previously been observed by others in both Brazil 13,15,16 and other countries. 4,6,25 Inequalities in access to and the quality of prenatal care might somehow explain the higher exposure of children belonging to the less privileged classes to the risk of CS.…”
Section: Discussionsupporting
confidence: 55%
“…Other authors have reported that sexual transmission seems to be an important HBV transmission route in areas of low endemicity 19,25,26 . In the current study, however, unprotected sex with multiple partners and previous STDs were not signifi cantly associated with HBV infection in the adjusted analysis, even though previous STDs were associated in the bivariate analysis.…”
Section: Discussionmentioning
confidence: 94%
“…Although several studies have been conducted on hepatitis B and C, especially on blood banks 6,7,8,9,10,11,12 , there are few studies carried out among the general population 13,14,15 , and due to territorial extension, and cultural and economic differences, the distribution of these diseases in the country differs among regions 16 .…”
Section: Introductionmentioning
confidence: 99%